UPAYA MENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 1 MATAN HILIR UTARA - Rusihan, Rusihan; Bistari, Bistari (Jurnal Kajian Pembelajaran dan Keilmuan, 2019)
Abstract The research was conducted in two cycles. Each cycle has different planning, implementation, observation and reflection. The research subjects are principals and teachers. The school principal with his academic supervision action, while the teacher of SMP Negeri 1 Mantan Utara downstream as an object as well as a subject in providing academic supervision treatment. Data analysis techniques that guide data processing using the percentage of 40 (%) achievement with a constant of 100. To see the interpretation using the score interpretation criteria to strengthen interpretation in the following conclusions: 80% - 100% (Excellent), 66% - 79 % (Good), 56% - 65% (Sufficient), and 40% - 55% (Less). The results showed that the ability of teachers in the implementation of the learning process experienced an increase in the percentage at each stage, from the first cycle to an average of 63% (enough) and in the second cycle an average of 68% (good). There is an increase in the ability of teachers by 5% from cycle I. In detail there was a significant increase in the initial conditions of the school when compared to the final state in cycle II. The accuracy of teachers entering the classroom increased by 48%, the use of learning media increased by 32%, varied methods increased by 31%, and learning strategies increased by 36%. Keywords: Pedagogical Competence, Academic Supervision, and Improving